The Qur’anic quote in the poetry of Al-Abbas bin Al-Ahnaf (d. 193 AH) Analytical study (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the master of the Messengers, the Prophet Muhammad, the Chosen One. And upon his good and pure family, and his companions, the valiant. As for after... The Holy Qur’an is the miracle of Islam, an ocean, before which stood helpless those who confronted it. It is eloquence.Rhetoric and rhetoric are a style that has a great impact on enchanting souls, astounding minds, and enlightening hearts. and straightening tongues. The poets were not unaware of its magnificence, as they drew from this fleeting well to establish sources their culture. And Al-Abbas bin Al-Ahnaf is only one of those, whose Quranic influence was prominent in his poetry.